2018
DOI: 10.1103/physrevb.98.144519
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of nodeless multiband superconductivity and particle-hole crossover in the vortex cores of FeTe0.55Se0.45

Abstract: Scanning tunneling experiments on single crystals of superconducting FeTe 0.55 Se 0.45 have recently provided evidence for discrete energy levels inside vortices. Although predicted long ago, such levels are seldom resolved due to extrinsic (temperature, instrumentation) and intrinsic (quasiparticle scattering) limitations. We study a microscopic multiband model with parameters appropriate for FeTe 0.55 Se 0.45 . We confirm the existence of well-separated bound states and show that the chemical disorder due to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Recently, based on theoretical simulations of an effective low-energy Hamiltonian it was suggested that Majorana hybridization in conjunction with a realistic distribution of disordered vortex sites, offers an explanation of the decreasing number of ZEPs with increasing magnetic field [408,418]. Earlier theoretical studies investigated the role of random Se/Te substitution on the vortex bound states, finding insignificant effects from this kind of isovalent disorder [419]. It was shown how disorder in vortex locations is important for smearing out oscillations in the field dependence of the density of zero-energy peaks.…”
Section: Experimental Evidence For Majorana Zero Modes: Vortex Statesmentioning
confidence: 99%
“…Recently, based on theoretical simulations of an effective low-energy Hamiltonian it was suggested that Majorana hybridization in conjunction with a realistic distribution of disordered vortex sites, offers an explanation of the decreasing number of ZEPs with increasing magnetic field [408,418]. Earlier theoretical studies investigated the role of random Se/Te substitution on the vortex bound states, finding insignificant effects from this kind of isovalent disorder [419]. It was shown how disorder in vortex locations is important for smearing out oscillations in the field dependence of the density of zero-energy peaks.…”
Section: Experimental Evidence For Majorana Zero Modes: Vortex Statesmentioning
confidence: 99%
“…As discussed in Section I, several compounds of iron-based superconductors naturally meet these requirements (Fig. 1(a)) [237][238][239][240][241][242].…”
Section: A Vortex Bound State With Topologymentioning
confidence: 99%
“…S12 for the details). However, because Se and Te are isovalent, the spatial inhomogeneity of the chemical potential should be very small (36). Only the vortex distribution is the main physical factor affecting the LDOS of the vortex cores.…”
Section: S C I E N C E a D V A N C E S | R E S E A R C H A R T I C L Ementioning
confidence: 99%